EFEKTIFITAS ROM AKTIF ASISTIF SPHERICAL GRIP TERHADAP PENINGKATAN KEKUATAN OTOT EKSTREMITAS ATAS PASIEN STROKE DI RUANGAN NEUROLOGI RUMAH SAKIT STROKE NASIONAL BUKITTINGGI TAHUN 2015 - Muhammad Arif; Gusni Hanila (LPPM UNIVERSITAS PERINTIS INDONESIA, 2015)
Stroke is the third leading cause of death in developed countries, after heart disease and cancer. Approximately 2.5 % died and the remainder mild or severe disability. Stroke caused many problem. One of the effect that occur in stroke patients was exsperiencing weakness on one side of the body. Therefore, stroke patients require a rehabilitation by exercises range of motion / ROM. Exercises to stimulate the movement of the hand which one form of the training is an practice in functional grasping hand. ROM spherical grip exsercises performed in actively and assistively. This study aims to find out the effectiveness of active-assistive ROM: spherical grip of an increase in upper extremity muscle strength in stroke patients in hospitals Stroke Bukittinggi. The design study is a quasy exsperiment for 7 day with treatment 2 times a day. Sample taken were 18 respondents by measuring muscle stregth before and after intervension. The results of statistical paired sample T- Test obtained average of p values 0.000. Therefore can be concluded that there is an incease in muscle stregth between before and after active-assistive ROM exercise: spherical grip. The results could be an input for nurses to make physical exercises range of motion moment as one of the independent nursing intervention in hospitals Stroke Nasional Bukittinggi and intervention in the treatment of stroke.